Bismuth Silicate/Silica-Titania Synthesis from In Situ Decomposition of Oil Palm Leaves as Silica Source - Salprima Yudha S; Morina Adfa; Swadexi Istiqphara; Muhamad Alvin Reagen (Science and Technology Indonesia, 2023)
In this work, bismuth silicate-titania has been synthesized in two stages by utilizing bismuth oxynitrate as an elemental source of bismuth, oil palm leaves (OPL) as a source of silica and titanium tetraisopropoxide (TTIP) as source of titania (TiO2). In the first stage,bismuth silicate/silica (Bi4Si3O12/SiO2) was formed, which occurs due to the in-situ decomposition of palm leaves and reacts directly with the bismuth precursor at high temperatures (900oC). The reaction could possibly occur through a solid-state reaction mechanism between bismuth oxide and silica or through a more complex mechanism within the reaction mixture. The resulting product then reacts with TTIP, which is added and heated at the same temperature to form Bi4Si3O12/SiO2-TiO2 (bismuth silicate/silica-titania). Characterization of the as-prepared product using X-ray diffraction showed the dominance of bismuth silicate and small amount of titania (TiO2). As a result, TiO2 could not be detected in the diffractogram. Nevertheless, an analysis using energy-dispersive X-rays showed the presence of titanium elements in the resulting composite. The results of this study can be used to develop ternary metal oxides based on natural resources and agricultural wastes, such as oil palm leaves.